2020
DOI: 10.1007/s10880-020-09711-x
|View full text |Cite
|
Sign up to set email alerts
|

Self-help Acceptance and Commitment Therapy for Carers of People with Multiple Sclerosis: A Feasibility Randomised Controlled Trial

Abstract: Acceptance and Commitment Therapy (ACT) is an established psychological therapy, but its effectiveness for carers of people with multiple sclerosis (MS) experiencing carer-related strain has not been established. This study assessed the acceptability and feasibility of conducting a randomised controlled trial comparing ACT self-help, telephone-supported ACT self-help, and usual care. We describe a mixed-method, parallel three-armed feasibility randomised controlled trial. Participants were carers (i.e. caregiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Participants were parents of children with asthma in Chong et al. and family caregivers of people with multiple sclerosis in Potter et al. (2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were parents of children with asthma in Chong et al. and family caregivers of people with multiple sclerosis in Potter et al. (2020).…”
Section: Resultsmentioning
confidence: 99%
“…The included 2 RCTs tested the effects of ACT interventions on quality of life of family caregivers, compared to either a treatment as usual control group (Potter et al, 2020) or an attention control group providing education (Chong et al, 2019). Participants were parents of children with asthma in Chong et al and family caregivers of people with multiple sclerosis in Potter et al (2020). While the intervention in Chong et al involved 4 weekly face-to-face ACT sessions delivered in a group format, the intervention in Potter et al was ACT self-help workbook with 8 weekly chapters with weekly telephone support.…”
Section: Effects Of Act On Quality Of Lifementioning
confidence: 99%
“…The earliest of these papers was published in 2007. The purpose of the interventions varied: improving health literacy (Jafari et al., 2020); developing caregiver knowledge and skills on a range of topics such as coping strategies, emotional support, providing practical assistance, MS knowledge (Alimohammadi et al., 2015; Coles et al., 2007; Finlayson et al., 2009; Jafari et al., 2020); acceptance and commitment therapy (Potter et al., 2021); a resilience‐based telehealth program (Halstead et al., 2020) and a collaborative care model (Rakhshan et al., 2018). Most of the interventions were delivered in a group format over five to eight sessions completed over 1–12 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Some interventions were delivered in blocks of 1–2 hr at a time, while other interventions occurred in a single day. Two interventions were delivered in an individualised format (Halstead et al., 2020; Potter et al., 2021). Only one intervention targeted child caregivers (Coles et al., 2007); others targeted adult caregivers.…”
Section: Resultsmentioning
confidence: 99%
“…With regards to carers, Losada et al (2015) found that 8-weekly, individual, face-to-face sessions improved depressive symptoms among carers of people with dementia. A self-help form was an effective intervention for carers of people with MS (Potter et al, 2020), whereas web-based ACT was effective for carers of people with cancer (Köhle et al, 2015). In addition, a blended support program of face-to-face contact, telephone support and online modules based on ACT increased feelings of control in people caring for partners with Amyotropic Lateral Sclerosis and Progressive Muscular Atrophy (De Wit et al, 2020).…”
Section: Introductionmentioning
confidence: 99%